1999
DOI: 10.1128/iai.67.10.5417-5426.1999
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Accessibility of an Inner Core Lipopolysaccharide Epitope ofNeisseria meningitidis

Abstract: We investigated the conservation and antibody accessibility of inner core epitopes of Neisseria meningitidislipopolysaccharide (LPS) because of their potential as vaccine candidates. An immunoglobulin G3 murine monoclonal antibody (MAb), designated MAb B5, was obtained by immunizing mice with agalE mutant of N. meningitidis H44/76 (B.15.P1.7,16 immunotype L3). We have shown that MAb B5 can bind to the core LPS of wild-type encapsulated MC58 (B.15.P1.7,16 immunotype L3) organisms in vitro and ex vivo. An inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 74 publications
0
50
0
1
Order By: Relevance
“…L3 strain MC58) or absent (L7-L12 immunotypes), the phenotype was B5+. We were also able to shed light on a previous and puzzling observation of phase variation of the B5+ serogroup B strain BZ157 (Plested et al, 1999). Sequencing of the homopolymeric tract within the lgtG gene of colony variants of this strain revealed that the lgtG gene was out of frame (nine C residues) in a B5+ colony and in frame (11 C residues) in a B5-colony (Table 1).…”
Section: The B5+ Phenotype Requires Lpt-3 But Is Rendered Phase Variamentioning
confidence: 61%
See 3 more Smart Citations
“…L3 strain MC58) or absent (L7-L12 immunotypes), the phenotype was B5+. We were also able to shed light on a previous and puzzling observation of phase variation of the B5+ serogroup B strain BZ157 (Plested et al, 1999). Sequencing of the homopolymeric tract within the lgtG gene of colony variants of this strain revealed that the lgtG gene was out of frame (nine C residues) in a B5+ colony and in frame (11 C residues) in a B5-colony (Table 1).…”
Section: The B5+ Phenotype Requires Lpt-3 But Is Rendered Phase Variamentioning
confidence: 61%
“…About 70% of Nm strains have an inner core LPS structure that binds mAb B5. An essential structural requirement of the epitope recognized by mAb B5 is PEtn attached specifically at the 3-position (PEtn-3) of HepII (Plested et al, 1999). To investigate further the genetic basis of this inner core LPS epitope and, in particular, the gene(s) required for the addition of PEtn-3, a recently developed method for mutagenesis was used (Tang et al, 2001) to identify mutants with either gain or loss of mAb B5 reactivity using appropriate Nm strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains BZ157 and NGH15 are from the culture collection of E. R. Moxon. LPS was extracted by the hot phenol/water method as described previously and purified from the aqueous phase by ultracentrifugation (45K, 4°C, 5 h) [11] yielding 200 mg in each case. O-deacylated LPS was prepared as described previously [13] in 50% yield from the LPS.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%